The Impact of ACTN3 Gene Polymorphisms on Susceptibility to Exercise-Induced Muscle Damage and Changes in Running Economy Following Downhill Running - de Lima, Leonardo Coelho Rabello [UNESP]; Bueno Junior, Carlos Roberto; de Oliveira Assumpção, Claudio [UNESP]; de Menezes Bassan, Natália [UNESP]; Barreto, Renan Vieira [UNESP]; Cardozo, Adalgiso Coscrato [UNESP]; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP] (Frontiers, 2021)
This study aimed to investigate if ACTN3 gene polymorphism impacts the susceptibility to exercise-induced muscle damage (EIMD) and changes in running economy (RE) following downhill running. Thirty-five healthy men were allocated to the two groups based on their ACTN3 gene variants: RR and X allele carriers. Neuromuscular function [knee extensor isometric peak torque (IPT), rate of torque development (RTD), and countermovement, and squat jump height], indirect markers of EIMD [muscle soreness, mid-thigh circumference, knee joint range of motion, and serum creatine kinase (CK) activity], and RE (oxygen uptake, minute ventilation, blood lactate concentration, and perceived exertion) for 5-min of running at a speed equivalent to 80% of individual maximal oxygen uptake speed were assessed before, immediately after, and 1–4 days after a 30-min downhill run (−15%). Neuromuscular function was compromised (P < 0.05) following downhill running with no differences between the groups, except for IPT, which was more affected in the RR individuals compared with the X allele carriers immediately (−24.9 ± 6.9% vs. −16.3 ± 6.5%, respectively) and 4 days (−16.6 ± 14.9% vs. −4.2 ± 9.5%, respectively) post-downhill running. EIMD manifested similarly for both the groups except for serum CK activity, which was greater for RR (398 ± 120 and 452 ± 126 U L–1 at 2 and 4 days following downhill running, respectively) compared with the X allele carriers (273 ± 121 and 352 ± 114 U L–1 at the same time points). RE was compromised following downhill running (16.7 ± 8.3% and 11 ± 7.5% increases in oxygen uptake immediately following downhill running for the RR and X allele carriers, respectively) with no difference between the groups. We conclude that although RR individuals appear to be more susceptible to EIMD following downhill running, this does not extend to the changes in RE.
Keywords: ACTN3; downhill; gene polymorphism; muscle damage; recovery; running; running economy; strength